Lack of conspecific visual discrimination between second-year males and females in the Saffron Finch - Benitez Saldivar, Maria Juliana (2018)
Sexually dichromatic birds often show delayed plumage maturation, but second-year (SY) males may or may not be distinguishable from females. In competitive contexts, SY males receive a reduced amount of adult males’ aggression, either by mimicking females or through signaling their sex and inexperience as subordinate males. To the human eye, reproductive dull SY male Saffron Finches are indistinguishable from females, whereas after second-year (ASY) males are golden yellow. Our aim is to establish whether SY males are sexually dichromatic with females to the eye of conspecifics. We describe plumage variation in females, SY and ASY males and, in particular, analyze assortative mating by color by comparing a previously disregarded yellow feather patch shared by the three groups. We measured plumage reflectance of the forehead, breast, belly, and axillaries, and used a two-step avian visual model analysis to estimate the ability of Saffron Finches to distinguish between SY males and females. We find that those groups are indistinguishable to conspecifics by color. Furthermore, we find non-significant evidence of assortative mating directly related to the coloration of comparable feather patches between females and each type of male, though body condition of SY males is associated to that of their mates. Our results are compatible with both the female-mimicry and the status signaling hypotheses of evolution and maintenance of delayed plumage maturation. However, the singing behavior of males reveals their presence within the breeding site; the combined effect of song and dull coloration suggest that SY males are honestly revealing their sex and status to conspecifics.